PERAN CAMAT DALAM MENGOORDINASIKAN KETENTRAMAN DAN KETERTIBAN UMUM DI KECAMATAN KAMPAR KABUPATEN KAMPAR - Mulyadi, Robi; Mochtar, Erman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This Study almed to determine the role of Kampar district head in coordinate security and public order inthe district of Kampar, Kampar regency. This study is focused on the district head of the Kampar because considering the dostrict head given task is to coordinate the security and order. The issues of security and order in the district of Kampar had increase from 2012 to 2013. The role of district head’s in coordinating security and public order in the distric of Kampar which is based on the basic tasks of district head whhich has been mandated by law. In the implementation, there are still constraints faced by the district head in coordinating security an public order with the relevan agencies. Based on this background, the study and public order in the district of Kampar, and what are the factors of less optimal of district head’srole in coordinating the implementation of security and public order in the district of Kampar, Kampar regency.This research is descriptive in wich research provides a description or picture of the phenomenon or social phenomenom studied by describing the independent variables systematically and accurately. Method of data collection is with In-depth interview and study documentation. The result of study indicate that the role of tge district head’s in coordinating security and public order in the district of Kampar, Kampar regency based on task assignment regulated by law. In the implementation inter-agency between the agencies found that there are lack of coordination with each other. Whereas, the synergy of each agency is required in the administration of public security and order in the district of kampar, Kampar regency.Keywords : Role, District, Security and Public Order